Wireless, skin-attachable patch with 3D liquid metal electrodes for vagus nerve stimulation in depression - Wonjung Park; Enji Kim; Doo-Ho Kang; Sumin Kim; Yeon-Mi Hong; Dayeon Kim; Jakyoung Lee; Hayoung Song; Hyun Ho Jung; Dahl-Young Khang; Jung Ah Lim; Jang-Ung Park (Proceedings of the National Academy of Sciences, 2026)
Current nonsurgical vagus nerve stimulation (VNS) approaches often suffer from broad current spread, high electrode-skin impedance, and unintended stimulation of surrounding tissues, which can reduce efficacy and cause side effects. Here, we present a wirelessly operable, skin-attachable VNS patch with three-dimensional liquid-metal electrodes that mimic the low modulus of biological tissues, developed as a minimally invasive platform for investigating the biological mechanisms underlying VNS in a mouse model of depression. The soft, low-modulus three-dimensional liquid metal electrodes gently penetrate the skin, bypass the stratum corneum, and improve electrode–tissue coupling while minimizing tissue damage compared with conventional planar or rigid electrodes. To comprehensively assess therapeutic effects, we conducted behavioral tests, neural probe-based brain signal analysis, dendritic spine density measurements, and blood and inguinal lymph node profiling in depression model mice. VNS increased plasma serotonin levels and increased dendritic spine density, indicating improved neuroplasticity. Corticosterone-induced depressive mice exhibited elevated CD4+ and B220+ cells, which normalized with VNS. These results establish an animal-level proof-of-concept that minimally invasive VNS can engage key neural and immunological pathways relevant to depression, providing a foundation for future neuromodulation strategies.